Brassolis isthmia (Lepidoptera: Nymphalidae) in peach palm and coconut palm in Costa Rica. - Mexzón, Ramón G. (2011)
The lifecycle of Brassolis isthmia was studied under field andlaboratory conditions in Guapiles, Limon, Costa Rica. Thisstudy was carried out between September and November,1994, during an insect outbreak in a peach palm plantation.During the following years were conducted observations ofthe butterfly feeding activities on coconut palms, in severallocalities of the Caribbean slopes too. Several hundred eggsand larvae in the first instar were collected and placed ingroups of ten individuals, and fed with pieces of peach palmleaves of 30 x 80 mm. The number of larvae necessary tocause defoliations of 5 and 20% was calculated for eachlarval developmental stage. Average development took 159days, distributed as follows: egg 20, larval 114, pupal 20, andadult 5 days. The larvae are gregarious, feed during the nightand remain during the day in nests constructed with debris ofdry leaves and silk. The consumption rate during the larvalstage was of 820.62 cmÇ; the seventh instar accounts for72.8% of this.